Սուրբ Բարդուղիմեոս առաքյալի ավանդույթը հայ-լատին և հայ-բյուզանդական եկեղեցական հարաբերությունների համատեքստում (X դ.-XIII դ. կեսեր) - Թորոսյան, Վահե Հ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В 40-х гг. XIII в. в армяно-латинских церковных отношениях произошли значительные изменения. В этот период Папа римский настаивал на том, чтобы Католикос Всех Армян признал его верховенство. Свое главенство над Вселенской церковью Папа римский обосновывал тем, что он является наместником святого Петра, первоверховного апостола. В ответ на это Армянская Церковь подчеркнула, что была основана апостолами Фаддеем и Варфоломеем. Чтобы ослабить позицию Армянской Церкви, Папа указал на то, что, по некоторым данным, святой Фаддей не был причислен к двенадцати ученикам Иисуса Христа. Настаивая на том, что основатель Армянской Церкви, апостол Фаддей, действительно был одним из двенадцати учеников Христа, армяне одновременно стали подчеркивать значение апостола Варфоломея. Согласно всем Евангелиям, Варфоломей был одним из двенадцати апостолов Христа. Следует отметить, что склонность к предпочтению Варфоломея перед Фаддеем возникла в Армянской Церкви уже в X веке в ответ на требования Византийской империи и Константинопольского патриархата признать их верховенство. In the 1240s, significant changes took place in the Armenian-Latin church relations. During this period, the Pope insisted that the Catholicos of All Armenians accept his supremacy. The Pope justified his supremacy over the Universal Church by claiming to be the vicar of St. Peter, the chief of the apostles. In response, the Armenian Church emphasized its apostolic lineage, tracing its foundation back to the apostles Thaddeus and Bartholomew. To undermine the Armenian Church's position, the Pope pointed out that, according to some accounts, Saint Thaddeus was not counted among the twelve disciples of Jesus Christ. In order to affirm that the founder of the Armenian Church, the apostle Thaddeus, was indeed one of the twelve disciples of Christ, the Armenians concurrently began to highlight the significance of the apostle Bartholomew. According to all the gospels, Bartholomew was one of the twelve apostles of Jesus Christ. It is worth noting that the inclination towards favoring Bartholomew over Thaddeus emerged in the Armenian Church as early as the 10th century, in response to the demands of the Byzantine Empire and the Patriarchate of Constantinople to recognize their authority.
Keywords: Հին և միջին դարերի պատմություն; Միջեկեղեցական հարաբերություններ